Generation Scheduling in Power Systems with Hydro Electric Plants - Palamarchuk, S. (Journal of Technology Innovations in Renewable Energy, 2014)
Medium-term generation scheduling is an important component of power systems operation and management. The traditional problem statement aimed at reducing the total production cost can hardly correspond to the market environment. The paper considers specific features of the problem statement for a wholesale electricity market environment. An approach is suggested to solve the problem on the basis of bi-level optimization models. Such models take into account possible distortion of economic and technical parameters of generating units. The proposed technique obtains equilibrium of the generation company’s interests to simulate the competitive behavior under the oligopoly electricity market. A mathematical statement of the problem supposes the application of a dynamic programming method. An algorithm for the stochastic dynamic programming application is developed. A numerical example is presented to demonstrate the applicability of the method and algorithm. The efficiency of the proposed approach is shown in comparison with the traditional generation scheduling technique.